2019
DOI: 10.1016/j.ajpath.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection and Cholangiocarcinoma

Abstract: Hepatitis C virus (HCV) infection is a global public health problem because it is a main cause of liver cirrhosis and hepatocellular carcinoma. This human oncogenic virus is also associated with the development of non-Hodgkin lymphoma and cholangiocarcinoma (CCA). The association between HCV infection and CCA has been examined in a number of epidemiologic studies. However, in vivo and in vitro results demonstrating the oncogenic mechanisms of HCV in CCA development and progression are insufficient. Here, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…There are a small number of studies investigating the relation between viruses and cholangiocarcinoma and mainly rely on an indirect approach, focused on the survival and prognosis of HBV-and/or HCV-infected patients. In this context, some potential mechanisms linking HCV and cholangiocarcinoma have been discussed by Navas et al [143]. A study by Zhou et al reported an odds ratio of 5.39 and 2.6 for HBV and HCV infection in IHCC, respectively [57].…”
Section: Bile Duct Cancermentioning
confidence: 99%
“…There are a small number of studies investigating the relation between viruses and cholangiocarcinoma and mainly rely on an indirect approach, focused on the survival and prognosis of HBV-and/or HCV-infected patients. In this context, some potential mechanisms linking HCV and cholangiocarcinoma have been discussed by Navas et al [143]. A study by Zhou et al reported an odds ratio of 5.39 and 2.6 for HBV and HCV infection in IHCC, respectively [57].…”
Section: Bile Duct Cancermentioning
confidence: 99%
“…Cholangiocarcinoma is divided into two main groups; intrahepatic cholangiocarcinoma (ICC) which represents about 10% of cholangiocarcinoma and extrahepatic cholangiocarcinoma (ECC) which includes perihilar and distal extrahepatic cholangiocarcinoma that account for 50 and 40% of cholangiocarcinoma, respectively [3,4]. Multiple risk factors for cholangiocarcinoma have been identified like primary sclerosing cholangitis, chronic viral hepatitis, liver cirrhosis, bile duct stone and choledochal cyst [5][6][7][8][9]. Other possible risk factors like diabetes mellitus, smoking, alcohol consumption and obesity are less established and still controversial with no clear mechanisms that explain their connection to cholangiocarcinoma [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the KEGG pathway enrichment results of the identified module genes also indicate their involvement in CCA pathogenesis. For example, hepatitis C virus (HCV) infection is identified as an important risk factor for the development of CCA (43); recent progress has shown that cellular senescent markers can distinguish cholangiocellular carcinoma from duct adenoma, implying a possible role in the pathophysiology of CCA (44,45). Additionally, cell cycle changes are particularly important for the growth of malignant tumors (42).…”
Section: Discussionmentioning
confidence: 99%